2005
DOI: 10.1007/bf02430263
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plasticiser on the lithium ionic conductivity of polymer electrolyte PVC-LiCF3SO3

Abstract: Abstract. Solid polymer electrolyte films based on poly(vinyl chloride)-lithium triflate (PVCLiCF3SO3) have been prepared by the solution-cast technique in various concentrations. The film with the highest conductivity was used to prepare plasticised polymer electrolyte films by using poly(ethylene glycol) (PEG) of different molecular weights, i.e., 200, 400 and 600 gmok ~. These films were prepared to study the effects of addition of low molecular weights PEG on the lithium ionic conduction of the PVC based p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Ionic conductivity of the designed binder films was evaluated by electrochemical impedance spectroscopy (EIS) analysis. [ 28 ] Like high ionic conductivity of polysaccharides, [ 29 ] the chitosan specimen showed relatively high ionic conductivity (8.17 × 10 −6 S cm −1 ), and the chitosan–XNBR films showed higher ionic conductivity with higher chitosan contents (Figure S4, Supporting Information). Considering the results of various analyses, the Li–S cell with X1C3 binder was expected to show the most improved battery performance at high C rates (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…Ionic conductivity of the designed binder films was evaluated by electrochemical impedance spectroscopy (EIS) analysis. [ 28 ] Like high ionic conductivity of polysaccharides, [ 29 ] the chitosan specimen showed relatively high ionic conductivity (8.17 × 10 −6 S cm −1 ), and the chitosan–XNBR films showed higher ionic conductivity with higher chitosan contents (Figure S4, Supporting Information). Considering the results of various analyses, the Li–S cell with X1C3 binder was expected to show the most improved battery performance at high C rates (Figure 2d).…”
Section: Resultsmentioning
confidence: 99%
“…With a view to gain sufficient insight into the transport phenomena occurring within polymer-salt complexes in general and triflate ion-based systems in particular, there was an increased thrust during the last decade towards investigating new matrices for improving ion-conducting characteristics as well as in their detailed structural characterization by means of Fourier transform infrared (FT-IR) spectral features. The favorable scope of vibrational spectroscopic data is therefore expected to provide an exquisite tool for probing into the structural and functional features of macromolecular systems and aggregates [14][15][16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%
“…As the concentration of plasticizer increases, the amorphous nature of the electrolyte increases, thus improving the ionic conductivity of the polymer electrolyte. Plasticizers of poly(ethylene glycol) (PEG) with different molecular weight, PEG 200 , PEG 400 , and PEG 600, showed that the conductivity of a polymer electrolyte decreases as molecular weight of plasticizer increases [19]. PEG 200 has the largest concentration of free ions associated only with the anti-symmetric stretching mode in the matrix polymer.…”
Section: Introductionmentioning
confidence: 99%